Estimate of background baseline and upper limit on the chiral magnetic effect in isobar collisions at sNN =200 GeV at the BNL Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2024)
For the search of the chiral magnetic effect (CME), STAR previously presented the results from isobar collisions (Ru4496+Ru4496, Zr4096+Zr4096) obtained through a blind analysis. The ratio of results in Ru+Ru to Zr+Zr collisions for the CME-sensitive charge-dependent azimuthal correlator (Δγ), normalized by elliptic anisotropy (v2), was observed to be close to but systematically larger than the inverse multiplicity ratio. The background baseline for the isobar ratio, Y=(Δγ/v2)Ru(Δγ/v2)Zr, is naively expected to be (1/N)Ru(1/N)Zr; however, genuine two- and three-particle correlations are expected to alter it. We estimate the contributions to Y from those correlations, utilizing both the isobar data and hijing simulations. After including those contributions, we arrive at a final background baseline for Y, which is consistent with the isobar data. We extract an upper limit for the CME fraction in the Δγ measurement of approximately 10% at a 95% confidence level on in isobar collisions at sNN=200GeV, with an expected 15% difference in their squared magnetic fields. © 2024 American Physical Society.
Keywords: dept.phy; peer-reviewed